1997
DOI: 10.1590/s1413-77391997000100006
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la ablacion peduncular en la maduracion gonadal de Pleoticus muelleri bate (decapoda, solenoceridae). I. interaccion entre muda y desarrollo ovarico

Abstract: . Abstract: The objective of this study was to compare the ovary development of ablated and non-ablated females of Pleoticus muelleri and to evaluate the influence of eyestalk ablation on molting frequency. The females (7-22 g weight) were maintained under culture conditions with 12:12 fotoperiod, l5-17°C temperature and 31%osalinity. They were fed on fresh squid, prawn and clam. The ovaries and digestive glands were weighed and fixed for histological examination at 4,9, 15,20, 40, and 50 days. Gonad index var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Individuals were weighed and tagged at the beginning of the experiment (Diaz et al 1997). Every 3 d the state of maturation was observed, selecting the shrimp with mature spermatophores for manual ejaculation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals were weighed and tagged at the beginning of the experiment (Diaz et al 1997). Every 3 d the state of maturation was observed, selecting the shrimp with mature spermatophores for manual ejaculation.…”
Section: Methodsmentioning
confidence: 99%
“…P. rnuelleri reaches more than 20 g in less than 5 mo (Fenucci et al 1990). The effect of eyestalk ablation on gonad maturation and molting has been studied in this species (Makinouchi et al 1995;Diaz et al 1996Diaz et al , 1997.…”
mentioning
confidence: 99%
“…The Aquaculture group from the University of Mar del Plata has been working with both species, but mainly with P. muelleri, on different aspects of the biology, nutrition, maturation, massive larval culture, and growth out in ponds. Some studies have demonstrated good survival and growth under culture conditions (Fenucci et al, 1983(Fenucci et al, , 1990Petriella et al, 1984;Díaz et al, 1996), and determined the nutritional requirements (Fernández-Gimenez & Fenucci, 2002;Romanos-Mangialardo & Fenucci, 2002) as well as gonadal maturation in captivity (Díaz et al, 1997(Díaz et al, , 2001Díaz & Fenucci, 2004), and characterized the digestive proteinases in relation to the molting cycle (Fernández-Gimenez et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it was filtered through 5 μm pore size cotton mesh. The experimental conditions were: temperature 18–20°C, salinity 31g L −1 , pH 7, ammonium <0.2 mg L −1 , 12 h light–12 h dark photoperiod, and light intensity 2 lx (Díaz et al 1996, 1997). Water was completely exchanged daily.…”
Section: Methodsmentioning
confidence: 99%
“…It supports important fisheries; however, fluctuations in catches have led to increasing the interest in this shrimp as a potential crop in temperate‐zone aquaculture. Preliminary experiments have demonstrated good survival and growth under culture conditions (Fenucci, Muller & Magnaterra 1990; Díaz, Petriella & Fenucci 1996) as well as gonadal maturation in captivity (Makinouchi, Sarlo, Díaz & Alvarez 1995; Díaz, Petriella & Fenucci 1997; Díaz, Fernández Giménez, Harán & Fenucci 2001).…”
Section: Introductionmentioning
confidence: 99%